Indonesians and their Arab world: guided mobility among labor migrants and Mecca pilgrims - Lücking, Mirjam (Southeast Asia Program Publications, an imprint of Cornell University Press, 2020)
"Tackles the problem of how to interpret the current conservative turn in Indonesian Islam by trying to understand how everyday Indonesians understand their relationship to the Arab world, directly considering the experiences of two groups of Indonesians who actually travel to the Arabian peninsula: pilgrims, and labor migrants"--